Varian Leksikon Bahasa Jawa Masyarakat Samin Desa Klopodhuwur Kabupaten Blora - bekti setio astuti (Jurnal CULTURE (Culture, Language, and Literature Review), 2014)
The Javanese language used by Samin community is something unique because it has a special significance with Samin community that is not understandable to the general public. It occurs as the socio-cultural aspects of Samin community is different from others. The problems formulated in this study are: (1) what Javanese lexicons used by Samin community in their daily life, and  (2) how Javanese lexicons are related to the socio-culture of Samin community . Several references used to discuss the issues, namely: socio-dialectology, distinctive dialect, variations in language, speech levels in Javanese language, Javanese lexicons, and the concept of Samin community culture.  Key words: socio-dialectology, Javanese lexicons, culture